(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This article proposes two fundamental objectives. Firstly, to give an idea about the conception that language teachers of eighth graders have of reading and the cognitive processes involved in this task; in other words, their metacomprensive knowledge. Secondly, to establish if this knowledge influences the concept of reading that their own students have already constructed. Furthermore, the paper investigates the perception a group of teachers on the student’s potential for performing this task. Five teachers ―whose students showed a high level of metacomprensive knowledge according to their age― and five other students ―whose student showed a low level of metacomprensive knowledge― were interviewed. In the analysis of these answers, we establish that the metacomprensive knowledge of the teachers not only influences that of their students but also optimizes the teacher’s perception of the possibility of acquiring reading expertise from his students.